Juridical Review of Independence Development in Class I Correctional Institutions in Surabaya - Dhyta Wahyu Setyawan; Adies (YURISDIKSI : Jurnal Wacana Hukum dan Sains, 2023)
The problem approach method is carried out using the sociological juridical method, namely by looking at how a legal institution is applied and enforced in practice and data obtained directly from the community. The results of the study show that the convict development program (especially independence development) has been implemented by Class I Correctional Institutions in Surabaya, but there are still obstacles in the implementation of the program caused by various factors. The benefits felt by convicts while undergoing skills training are increasing the knowledge of convicts in the field of skills, convicts can socialize with other convicts, fill their free time while in prison. Obstacles faced in carrying out convict coaching are limited time and human resources in this case the ability of a coach to carry out coaching as well as facilities and infrastructure that meet the criteria but are still inefficient in their utilization due to situations and conditions that sometimes prevent convicts from using some of the facilities.